The influence of mathematics anxiety and emotional quotient on English language education students’ statistics learning outcomes - Puspananda, Dian Ratna; Rahmawati, Oktha Ika (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2020)
The internal factors (characteristics) of students are assumed to have an impact on the learning process. Internal factors of students include motivation, creativity, intelligence, emotional intelligence, anxiety, etc. Most English language education students still worry about statistics course, which contains numbers and different calculation process types. However, the ‘statistics’ course is a compulsory subject that students must study, particularly at IKIP PGRI Bojonegoro, which is very useful to complete final and daily assignments. Statistics is a part of mathematics that studies how to access, analyze, and interpret data. Most English language education students find numbers-related topics difficult. Anxiety in subjects related to numbers is assumed to affect students' psychological state, especially emotional states, which is an important factor that leads to achievement. This study aimed to determine the effect of mathematics anxiety and emotional quotient on English language education students' statistics learning outcomes at IKIP PGRI Bojonegoro. The subjects in this study were the third-year students of English language education in 2019/2020. The technique of data analysis used was the Multiple Regression Analysis. The data were obtained from questionnaires and documentation. The results showed that mathematical anxiety and emotional quotient affect English Language Education students' statistics learning outcomes at IKIP PGRI Bojonegoro. This is evidenced by the value of Fcount = 69,992 higher than Ftable = 1,607. Mathematical anxiety and emotional quotient affect the statistics learning outcomes by 74.9% (strong category). Faktor internal (karakteristik) mahasiswa diduga dapat mempengaruhi proses pembelajaran yang dilakukan. Ada banyak faktor internal (karakteristik) mahasiswa diantaranya motivasi, kreatifitas, kecerdasan spiritual, kecerdasan emosi, kecemasan, dan lain-lain. Sebagian besar mahasiswa prodi pendidikan bahasa inggris masih merasa cemas dengan mata kuliah statistika yang banyak mengandung angka dan berbagai macam proses penghitungan. Padahal statistika wajib dipelajari oleh setiap mahasiswa khususnya di IKIP PGRI Bojonegoro karena merupakan mata kuliah wajib yang sangat bermanfaat dalam penyelesaian penulisan tugas akhir maupun kehidupan sehari-hari. Statistika merupakan bagian dari ilmu matematika yang mempelajari tentang cara memperoleh, menganalisis, dan menginterpretasikan data. Mahasiswa menganggap mata kuliah yang berhubungan dengan angka selalu sulit. Perasaan cemas pada mata kuliah yang berhubungan dengan angka tersebut diduga dapat memengaruhi kondisi psikis mahasiswa khususnya ranah emosi, padahal emosi merupakan faktor penting yang dapat mempengaruhi prestasi seseorang. Dari penjelasan tersebut tujuan dari penelitian ini adalah untuk mengetahui pengaruh mathematic anxiety dan emotional quotient terhadap hasil belajar statistika mahasiswa Pendidikan Bahasa Inggris IKIP PGRI Bojonegoro. Subjek pada penelitian ini adalah mahasiswa tingkat III tahun akademik 2019/2020. Teknik analisis data menggunakan Analisis Regresi Ganda. Data diperoleh melalui kuesioner dan dokumentasi. Hasil penelitian menunjukkan mathematic anxiety dan emotional quotient memengaruhi hasil belajar statistika mahasiswa Pendidikan Bahasa Inggris IKIP PGRI BOJONEGORO. Hal ini dibuktikan dengan nilai Fhitung = 69,992 lebih besar daripada Ftabel=1,607. Mathematic Anxiety dan emotional quotient memengaruhi hasil belajar statsitika mahasiswa pendidikan bahasa inggris sebesar 74,9%. Pengaruh mathematic anxiety dan emotional quotient sebesar 74,9% masuk dalam kategori kuat.